Asimilasi dialek Melayu Kelantan dan dialek Thai Kelantan dalam bahasa Cina Peranakan Kelantan (Jurnal Bahasa, 2005)
This article will discuss the structure of the language of the Kelantan Peranakan Chinese. Kelantan Peranakan Chinese is a group that has assimilated extensively in culture and language to Kelantan Malays and also Kelantan Thais. Some salient structural features which are borrowings from Kelantan Malay and Kelantan Thai dialect will be addressed within the frame-work of contrastive linguistics from the perspective of language contact. Some salient syntactic features of intraclausal and interclausal con-structions will be deliberated to exhibit the structure of the language of Kelantan Peranakan Chinese, which is a case of linguistic assimi-lation of Chinese-Malay-Thai language systems.